Faktor-Faktor yang Mempengaruhi Keputusan Pasien Memilih Jasa Pelayanan Kesehatan - Rita, Nova; Afconneri, Yudistira (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2019)
Demand for health services in indonesia has declined, many are less satisfied with the health services provided by the hospital. Several influential factors such as: quality of service and the marketing mix. If the perceived service meet sorexceeds the expectations of the patient, the patient will be satisfied and remain willing to establish long-term relationships with hospital as well as being loyal to the hospital. From 6 patients who were interviewed, 3 patients said they wanted to choose another hospital if requiring hospitalization in the future. The purpose ofthis study was to determine the relationship ofservice quality and loyalty marketing mixwiththe patient consideration related to satisfaction of hospital services at hasanuddin hospital south Bengkulu. The type of this research was descriptive analytic reserach. The population were patients who were treated in hasanuddin general hospital in the year 2014, where the samples were taken by using the inclusion criteria (worth studying criteria) as many as 171 people. Data were collected by using question naires and interviews. Data analysis was performed by using univariate and bivariatechi square at α 5%.this research has been conducted in may-june 2014, with the results: the majority(49.1%) of respondents believe that service quality was not good, small proportion(18.7%) of respondents believethat the marketing mixwas not good, a minority of respondents (35.1%) were less well argued about loyalty, a minority of respondents (33.9%) did not choose hasanuddin hospital care if needed hospitalized health services again. There was no significant relationship between the quality of health care with the patients choice related to health care (p =0.516), there was no significant relationship between marketing mix with patients decision in choosing health services (p =1.000), there was no significant relationship between patient loyalty with patients decision in choosing health services (p =0.697). Permintaan pelayanan kesehatan di indonesia semakin menurun, banyak kurang puas dengan pelayanan kesehatan yang diberikan oleh rumah sakit. Faktor berpengaruh : kualitas pelayanan dan bauran pemasaran. Dari 6 pasien diwawancara, 3 pasien mengatakan ingin memilih rumah sakit lain jika memerlukan jasa rawat inap lagi. Tujuan penelitian :untuk mengetahui hubungan kualitas pelayanan, bauran pemasaran dan loyalitas dengan keputusan pasien memilih jasa pelayanan kesehatan .jenis penelitian yaitu deskriptif analitik. Populasi adalah pasien yang dirawat di rsud hasanuddin damrah tahun 2014, sampel 171 orang.teknik pengumpulan data menggunakan kuesioner dan wawancara. Analisis data dilakukan secara univariat dan bivariat dengan chi square pada 5%. Penelitian dilaksanankan bulan mei-juni 2014 dengan hasil separuh (49,i%) responden berpendapat kualitas pelayanan adalah kurang baik, sebagian kecil (18,7%) responden berpendapat bauran pemasaran adalah kurang baik, sebagian kecil (35,1%) responden berpendapat loyalitas pasien adalah kurang baik, sebagian kecil (33,9%) responden tidak memilih rsud hasanuddin damrah jika membutuhkan pelayanan kesehatan rawat inap kembali. Tidak terdapat hubungan signifikan antara kualitas pelayanan dengan keputusan pasien memilih jasa pelayanan kesehatan (p= 0,516), tidak terdapat hubungan signifikan antara bauran pemasaran dengan keputusan pasien memilih jasa pelayanan kesehatan (p = 1,000), tidak terdapat hubungan signifikan loyalitas pasien dengan keputusan pasien memilih jasa pelayanan kesehatan (p= 0,697).